Multiple Kinase Involvement in the Regulation of Vascular Growth - Adderley, Shaquria P.; Joshi, Chintamani N.; Martin, Danielle N.; Mooney, Shayna; Tulis, David A. (New York: InTech Open Access Publishers, 2012)
The initial discovery of protein phosphorylation as a regulatory mechanism for the control of glycogen metabolism has led to intense interest of protein phosphorylation in regulating protein function (Cohen et al., 2001). Kinases play a variety of roles in many physiological processes within cells and represent one of the largest families in the human genome with over 500 members comprising protein serine/threonine, tyrosine, and dual-specificity kinases (Manning et al., 2002). Phosphorylation of proteins is one of the most significant signal transduction mechanisms which regulate intracellular processes such as transport, growth, metabolism, apoptosis, cystoskeletal arrangement and hormone responses (Bononi et al., 2011; Heidenreich et al., 1991; Manning et al., 2002; Pawson et al., 2000). As such, abnormal phosphorylation of proteins can be either a cause or a consequence of disease. Kinases are regulated by activator and inhibitor proteins, ligand binding, and phosphorylation by other proteins or via autophosphorylation (Hanks et al., 1991; Hug et al., 1993; Scott, 1991; Taylor et al., 1990; Taylor et al., 1992). Since kinases play key functions in many cellular processes, they represent an attractive target for therapeutic interventions in many disease states such as cancer, inflammation, diabetes and arthritis (Cohen et al., 2010; Fry et al., 1994; Karin, 2005; Mayers et al., 2005). In particular, the serine/threonine family of kinases comprises approximately 125 of the 500 family of kinases and includes the cyclic adenosine monophosphate (cAMP)-dependent protein kinase (PKA), the cyclic guanosine monophosphate (cGMP)-dependent protein kinase (PKG), and protein kinase C (PKC). These kinases are implicated in the regulation of cell growth and are the focus of this current study.